2012
DOI: 10.1007/s00167-012-2294-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anterior knee pain following total knee replacement: a systematic review

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 58 publications
6
81
1
Order By: Relevance
“…In the 6 to 10 year (median 7.9 years) follow-up study the mobile bearing knees did not sustain the difference in AKP that had been found in the short-term study [12,13] . These results are comparable to the findings of other systematic reviews and/or meta-analysis, most of which have not shown an advantage of using a mobile bearing [22,36,[48][49][50][51] . Based on these results combined with a recent metaanalysis showing less AKP in the mobile bearing TKA, it seems that the debate can be reopened as to whether the mobile bearing TKA is part of the solution to AKP [52] .…”
Section: Regeneration Of Nervessupporting
confidence: 87%
See 3 more Smart Citations
“…In the 6 to 10 year (median 7.9 years) follow-up study the mobile bearing knees did not sustain the difference in AKP that had been found in the short-term study [12,13] . These results are comparable to the findings of other systematic reviews and/or meta-analysis, most of which have not shown an advantage of using a mobile bearing [22,36,[48][49][50][51] . Based on these results combined with a recent metaanalysis showing less AKP in the mobile bearing TKA, it seems that the debate can be reopened as to whether the mobile bearing TKA is part of the solution to AKP [52] .…”
Section: Regeneration Of Nervessupporting
confidence: 87%
“…A key aim of this study was to identify literature evaluating the different determinants of AKP after a TKA was found [2,8,9,12,13,15,18,22,23,[25][26][27]30,34,[36][37][38][39][40][41] . The articles reviewed confirm this study's hypothesis that anything that alters the patellofemoral joint (PFJ) mechanics can activate these FNEs and thus induce AKP after TKA [22] . It can further be hypothesised that the nociceptive system can be activated by several factors, either alone or in combination: Hoffa impingement, peripatellar synovitis, increased osseous pressure and mechanical changes that alter the PFJ in an abnormal way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This condition reduces patient satisfaction and limits patient post-operative activity and is a common cause of revision surgery. 1,2 It was reported that 5-10% of patients had anterior knee pain after TKR. 3 Resurfacing or patellar non-resurfacing in TKR is still a controversial topic among surgeons.…”
Section: Introductionmentioning
confidence: 99%